Aspirin intake in the morning is associated with suboptimal platelet inhibition, as measured by serum Thromboxane B2, during infarct-prone early-morning hours. (3rd October 2019) - Racca, Cati; van Diemen, Jeske Joanna Katarina; Fuijkschot, Wessel Willem; Spit, Karlinde; Bonten, Tobias Nicolaas; Numans, Mattijs Everard; van der Bom, Johanna Gerarda; Smulders, Yvo Michiel; Thijs, Abel
Abstract: Aspirin is traditionally taken once daily in the morning and considered to be effective throughout the 24h interval. Cardiovascular events occur most frequently in the early morning, suggesting that these hours are critical in terms of adequate platelet inhibition. This study therefore assed platelet function in the early morning—8.00 AM—in healthy volunteers, during a once-daily (OD) 80 mg morning in comparison with an OD evening regimen and a twice-daily (BID) 40 mg regimen. It was an open-label randomized cross-over study, comprising 12 healthy subjects. Subjects were allocated to three sequential dosage regimens: 80 mg OD at 8.00 AM, 80mg OD at 8.00 PM, and 40 mg BID at 8.00 AM and PM. Platelet function 12 and 24 hours after aspirin intake was measured by means of serum thromboxane B2 (sTxB2 ) levels, the collagen/epinephrine closure time (Platelet Function Analyzer(PFA)-200 ® ) and the Aspirin Reaction Units (ARU, VerifyNow ® ). The results demonstrated that early morning sTxB2 concentrations were 5843pg in the morning regimen, 2877pg in the evening OD regimen, and 3343pg in the BID regimen (morning- vs evening regimen p = < 0.01; morning- vs BID regimen p = < 0.01). Early morning PFA-closure time ( p = 0.12)) as well as VerifyNow ARU ( p = 0.17) mean values were similar for all three regimens. In conclusion, the OD-morning regimen seems to acquire the lowest level of platelet inhibition during the critical early morning window. Switching to an OD-evening or BID intake seems prudent, although further research on clinical cardiovascular outcome in patients with stable cardiovascular disease is needed.